A technical report on the development, implementation and evaluation of an HIV/AIDS workplace policy and program on a farm in Mpumalanga : a South African case study - Doyer, Ida (Stellenbosch : Stellenbosch University, 2011)
Assignment (MPhil)--Stellenbosch University, 2005.